Interest rate bands of inaction and play-hysteresis in domestic investment: Evidence for the euro area - Ansgar Belke; Coletta Frenzel Baudisch; Matthias Göcke (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
The interest rate represents an important monetary policy tool to steer investment in order to reach price stability. Therefore, implications of the exact form and magnitude of the interest rate-investment nexus for the European Central Bank's effectiveness in a low interest rate environment gain center stage. We first present a theoretical framework of the hysteretic impact of changes in the interest rate on macroeconomic investment under certainty and under uncertainty to investigate whether uncertainty over future interest rates in the Euro area hampers monetary policy transmission. In this non-linear model, strong reactions in investment activity occur as soon as changes of the interest rate exceed a zone of inaction, that we call 'play' area. Second, we apply an algorithm describing path-dependent play-hysteresis to estimate investment hysteresis using data on domestic investment and interest rates on corporate loans for 5 countries of the Euro area in the period ranging from 2001Q1 to 2018Q1. We find hysteretic effects of interest rate changes on investment in most countries. However, their shape and magnitude differ widely across countries which poses a challenge for a unified monetary policy. By introducing uncertainty into the regressions, the results do not change much which may be due to the interest rate implicitly incorporating uncertainty effects in investment decisions, e.g. by risk premia. – – Der Zins ist ein wichtiges geldpolitisches Instrument zur Steuerung von Investitionen, um Preisstabilität zu gewährleisten. Im derzeitigen Niedrigzinsumfeld rücken Implikationen der genauen Gestalt und der Größenordnung des Zins-Investitions-Nexus für die Effektivität der Europäischen Zentralbank in den Vordergrund. Wir stellen zunächst den theoretischen Rahmen hysteretischer Effekte von Zinsänderungen auf makroökonomische Investitionen unter Sicherheit und unter Unsicherheit vor. Eine mögliche Störung des geldpolitischen Transmissionsmechanismus durch Unsicherheit über die Zinsentwicklung wird hierin untersucht. In diesem nicht-linearen Modell kommt es zu starken Reaktionen der Investitionsaktivität, sobald der Zins eine sogenannte Zone der Inaktivität verlässt, die wir 'play' nennen. Wir verwenden im Folgenden einen Algorithmus, welcher pfadabhängige play-Hysterese abbildet. Wir schätzen Zins-Hysterese unter Verwendung von Daten über inländische Investitionen und Zinsen auf Unternehmenskredite in 5 Ländern der Eurozone für den Zeitraum 2001Q1 bis 2018Q1. In den meisten Ländern finden wir hysteretische Effekte von Zinsänderungen auf Investitionen, deren Gestalt und Umfang sich nach Ländern stark unterscheiden. Dies stellt eine Herausforderung für eine gemeinsame Geldpolitik dar. Hingegen verändert die Berücksichtigung von Unsicherheitsvariablen die Ergebnisse kaum. Dies kann darauf zurückgeführt werden, dass Zinsen implizit - bspw. über Risikoaufschläge - bereits Unsicherheit in Bezug auf Investitionsentscheidungen beinhalten.
Keywords: C32; E44; E49; E52; F21; 330; European Central Bank; interest rate; investment; monetary policy; nonideal relay; pathdependence; play-hysteresis; uncertainty